Effect of multiple orifices of wave energy converter air columns towards overall turbine output - Nurul Afiqah Mohd Azhar,; Muhamad Aiman Jalani,; Mohd Rosdzimin Abdul Rahman,; Elyasabath Ghazali,; Mohd Kamarul Huda Samion,; Imai, Yasutaka; Mohd Rashdan Saad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigated a Wave Energy Converter (WEC) device known as the Backward Bent Duct Buoy (BBDB) by looking at the correlation between the number of orifices toward the power generation efficiency. The BBDB type of WEC has a major potential due to its design simplicity and relatively good performance. However, limited studies have been done regarding the BBDB device compared with other types of WEC, especially on the design of orifices. Thus, the objective of this study was to explore the effect of having a multiple number of orifices on the top panel of the BBDB device toward its power efficiency. It was achieved by designing and fabricating four BBDB top panels with varying number of orifices followed by experimental wave tank tests. The results showed that the top panel with 2 orifices produced the highest efficiency of 39% followed by the top panels with 4 orifices (27%), 1 orifice (23%) and 3 orifices (22%). This leads to the conclusion that top panels with multiple orifices promote better efficiency than single orifice.